Post-Judicial Review of Article 433: The Position of Persons with Disabilities in Making Agreements - Faradigma D Zainuddin (SEAN Institute, 2026)
Constitutional Court Decision No. 93/PUU-XX/2022 has fundamentally changed the construction of legal capacity for persons with disabilities in the Indonesian civil law system, which for more than a century and a half has been dominated by a discriminatory substitute guardianship regime. This study aims to analyze the transformation of legal capacity norms for persons with disabilities following the decision and examine the operationalization of the supported decision-making paradigm in contract law in Indonesia. This research is a normative legal study with a legislative approach, a conceptual approach, and a case approach. The results show that the Constitutional Court decision has given rise to three fundamental transformations: first, a change in the nature of guardianship from imperative (